1994
DOI: 10.1161/01.str.25.5.1071
|View full text |Cite
|
Sign up to set email alerts
|

Study of antiphospholipid antibodies in a patient with Sneddon's syndrome and her family.

Abstract: Sneddon's syndrome is a disease characterized by livedo reticularis and cerebrovascular lesions, with a hereditary transmission and unknown etiopathogenesis. A number of reports have documented a link between antiphospholipid antibodies and Sneddon's syndrome with different results. The present work was designed to sequentially study antiphospholipid antibodies in a patient with Sneddon's syndrome and her family and their potential role in thrombotic events. We used cardiolipin and a mixture of phospholipids f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…On the other hand Hess et al, (1993) determined by ELISA the amount of immunoglobulin binding to cerebral endothelium in patients with aPL and stroke, and demonstrated that these antibodies are distinct from those to cardiolipin. Lousa et al (1994) have also found a temporal relationship between LA and thrombosis, and in lupus erythematous Ferro et al (1994) suggest that a positive test for LA indicates a high thrombotic risk, whereas the presence of aCL alone may be indicative of low risk.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand Hess et al, (1993) determined by ELISA the amount of immunoglobulin binding to cerebral endothelium in patients with aPL and stroke, and demonstrated that these antibodies are distinct from those to cardiolipin. Lousa et al (1994) have also found a temporal relationship between LA and thrombosis, and in lupus erythematous Ferro et al (1994) suggest that a positive test for LA indicates a high thrombotic risk, whereas the presence of aCL alone may be indicative of low risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several multiplex families with the syndrome and aPL have been described [18][19][20] , including a large family with several individuals having sustained premature strokes [ 21 ] . In contrast, at least one family has been described with familial Sneddon syndrome in which the clinically affected individuals did not have any evidence for aPL, suggesting that Sneddon syndrome, at least in some cases, might be a separate clinical entity from classic APS [ 22 ] .…”
Section: Multiplex Antiphospholipid Syndrome Familiesmentioning
confidence: 99%
“…The diagnosis put forward by the pathologists was of vas cular nephrosclerosis of an arteriosclerotic nature. antibodies may be difficult to detect and they had been occasionally found in family members of patients with them [13,14], The echocardiogram showed minor mitral valvular abnormalities, which, even though of no functional signif icance, has also been found in other patients [15], A skin biopsy performed on the usual area [8] was normal. The reduction in creatinine clearance has also been found in other patients [8] which suggests that there is renal involvement in these patients as well.…”
Section: Auxiliary Diagnostic Toolsmentioning
confidence: 99%